The Study Of Cargoes From Tanjung Simpang Mengayau Wreck And Jade Dragon Wreck, Kudat, Sabah - Masbaka, Masyella (2023)
This thesis discusses the analysis and classification of artefacts recovered from cargoes of two ancient shipwrecks in Kudat, Sabah, Malaysia. On the basis of stylistic analysis of the ceramics from each ship, these ceramics are presumably dated around 10th to 13th centuries CE. The objectives of this study are (1) to produce a documented data to evaluate cargoes from the two ships, (2) to classify the recovered artefacts using scientific analysis and morphological study and (3) to date and identify the provenance of the cargoes. The first shipwreck is known as Tanjung Simpang Mengayau Wreck (TSM) and is believed to have sunk on its way from China to Borneo and/or Sumatera during the Northern Song Dynasty (960-1127 CE), while the second shipwreck, Jade Dragon Wreck (JDW) is dated to the Southern Song Dynasty (1127-1279 CE) judging from the similar artefacts found in Sumatera. The cargoes consist of earthenware, stoneware, porcelain and metal objects such as mirror discs and wall ornaments. The latter site also carried lithic artefact, which assemblage is absent at the former site. Analysis and classification of the ceramic cargo included 2,590 samples from the Department of Sabah Museum’s collection and private collectors in Sabah.